Analysis of Fundamental Aspects in Game Character Design - Clive Anderson (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2024)
The creation of a commercially successful game comes with many different considerations, such as its variety of content, overall cohesion, capacity of social interactions to name a few of the most important features. They are also well-packaged in a visual format, character designs being the highlight. The researchers have proposed to further understand the strategies employed by commercially successful games on the creative process of character design. Using a discussion-based-qualitative approach, the research will be composed of interviews with experienced concept artists from different sociocultural backgrounds, as well as literary sources to be complementary materials. This research will focus on the comparison between the general thought process and workflow that different concept artists have in creating a compelling character design to try to generate a general foundation for up and coming game concept artists. Further studies can be done to explore more perspectives on the topic to create a more compelling guideline overall.